Closing the Gender Gap?: New Spaces of Cultural Memory Construction for Contemporary Female Authors in Portugal - Bozkurt, Suzan (Cadernos de Literatura Comparada (teste), 2016)
This study is an exploration of feminist and non-essentialist, universal memory spaces for contemporary female authors in Portugal. It is based on the representations of four writers, Hélia Correia, Teolinda Gersão, Lídia Jorge and Inês Pedrosa in academic, press and online criticism. This study shows how a national critical language that re-enforces gender normativity in categorizations that often only leave the outside position of ‘escrita feminina’ to the majority of contemporary authors is counter-acted in a world literary space, where women writers’ work is judged and valued through other ideological and socio-cultural lenses that make the emergence of different and differing ‘regimes of value’ possible. Press and online critical localities represent a more flexible, fluid and multi-faceted space, where critical contextualizations are constantly overwritten, preventing static categories that can then be ‘naturalized’. Authors themselves can influence press and online critical commentary in performative acts as well as through the creation of an authorial ‘online self’, which creates a counter-memory to the traditional contextualizations in a national field that follow normative constructions rooted in a patriarchal discourse. On the one hand, a traditional elitist critical approach can be observed in all media, academic, press and, digital, that often misreads and omits women’s literary projects. On the other hand, female and feminist spaces of alternative constructions of cultural memory are also present and traditional contextualizations co-exist with new classificatory mechanisms that give a more adequate representation to contemporary female authorship.